Accuracy of gypsum casts after different impression techniques and double pouring - Silva, Stephania Caroline Rodolfo [UNESP]; Messias, Aion Mangino [UNESP]; Abi-Rached, Filipe De Oliveira [UNESP]; De Souza, Raphael Freitas; Reis, José Maurício Dos Santos Nunes [UNESP] (Public Library of Science (PLoS), 2016)
This study evaluated the accuracy of gypsum casts after different impression techniques and double pouring. Ten patients were selected and for each one it was obtained 5 partial putty/wash impressions with vinyl polysiloxane (VPS) material from teeth #13 to #16 with partial metal stock trays. The following techniques were performed: (1) one-step; two-step relief with: (2) PVC film; (3) slow-speed tungsten carbide bur and scalpel blade, (4) small movements of the tray and (5) without relief - negative control. The impressions were disinfected with 0.5% sodium hypochlorite for 10 minutes and stored during 110 and 230 minutes for the first and second pouring, respectively, with type IV gypsum. Three intra-oral lateral photographs of each patient were taken using a tripod and a customized radiographic positioner. The images were imported into ImageJ software and the total area of the buccal surface from teeth #13 to #16 was measured. A 4.0% coefficient of variance was criterion for using these measurements as Baseline values. The casts were photographed and analyzed using the same standardization for the clinical images. The area (mm2) obtained from the difference between the measurements of each gypsum cast and the Baseline value of the respective patient were calculated and analyzed by repeated-measures two way-ANOVA and Mauchly's Sphericity test (α = 0.05). No significant effect was observed for Impression technique (P = 0.23), Second pouring (P = 0.99) and their interaction (P = 0.25). The impression techniques and double pouring did not influence the accuracy of the gypsum casts.